THE EFFECTIVENESS OF FARMER CAPING LEARNING MEDIA ON JUNIOR HIGH SCHOOL STUDENT LEARNING OUTCAMES - suwandana, engkin (Universitas Hamzanwadi, 2020)
AbstractLearning material about facts and opinions is still difficult for grade VIII students because there is no media that supports interesting learning activities. For this reason, farmer caping media were chosen in learning facts and opinion sentences for supporting sociological and geographical reasons. said the farmer in this study is the acronym for the sentence game fakTA and opiNI (Farmers). The type of research that will be used in this research is experimental research with the method of developing the R&D model (research and development). This development research uses the Four-D-Model (4D) model. This 4D model has four stages, namely (1) Define; (2) Design; (3) Develop ; and (4) Disseminate. The sample in this research is 48 student of class VIII SMP Negeri 3 Gondang in Mojokerto-Jawa Timur. The instruments used in this study were student response questionnaire sheets, teacher and student activity observation sheets, and learning outcomes tests. Student learning outcomes in the form of test scores were analyzed with the help of commercial software to determine the effectiveness of the class that applied the learning media used during the teaching and learning process. The results show that the use of learning media in the form of farmer hat is very effective (applied to the experimental class) compared to conventional learning (in the control class). The pre-test and post-test mean scores in the experimental class were 49.17 and 85.83, respectively, while those in the control class were 64.58 and 79.17. The difference between the mean pre-test and post-test scores between the experimental class and the control class was 36.66 and 14.59, respectively. Meanwhile, the significance value of the two classes is 0.000 (sig.2-tailed) less than 0.05